Late Neogene evolution of the Peruvian margin and its ecosystems: a synthesis from the Sacaco record - Ochoa D. (2021)
The highly productive waters of the Humboldt Current System (HCS) host a particular temperate ecosystem within the tropics, whose history is still largely unknown. The Pisco Formation, deposited during Mio-Pliocene times in the Peruvian continental margin has yielded an outstanding collection of coastal-marine fossils, providing an opportunity to understand the genesis of the HCS ecosystem. We present a comprehensive review, completed with new results, that integrates geological and paleontological data from the last 10 My, especially focusing on the southern East Pisco Basin (Sacaco area). We discuss the depositional settings of the Pisco Formation and integrate new U/Pb radiometric ages into the chronostratigraphic framework of the Sacaco sub-basin. The last preserved Pisco sediments at Sacaco were deposited ~ 4.5 Ma, while the overlying Caracoles Formation accumulated from ~ 2.7 Ma onwards. We identified a Pliocene angular unconformity encompassing 1.7 My between these formations, associated with a regional phase of uplift. Local and regional paleoenvironmental indicators suggest that shallow settings influenced by the offshore upwelling of ventilated and warm waters prevailed until the early Pliocene. We present an extensive synthesis of the late Miocene–Pleistocene vertebrate fossil record, which allows for an ecological characterization of the coastal-marine communities, an assessment of biodiversity trends, and changes in coastal-marine lineages in relation to modern HCS faunas. Our synthesis shows that: (i) typical endemic coastal Pisco vertebrates persisted up to ~ 4.5 Ma, (ii) first modern HCS toothed cetaceans appear at ~ 7–6 Ma, coinciding with a decline in genus diversity, and (iii) a vertebrate community closer to the current HCS was only reached after 2.7 Ma. The genesis of the Peruvian coastal ecosystem seems to be driven by a combination of stepwise transformations of the coastal geomorphology related to local tectonic pulses and by a global cooling trend leading to the modern oceanic circulation system. © 2021, Geologische Vereinigung e.V. (GV).